2017
DOI: 10.1016/j.gloplacha.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Drought impacts on vegetation activity in the Mediterranean region: An assessment using remote sensing data and multi-scale drought indicators

Abstract: The present work analyzes the drought impacts on vegetation over the entire Mediterranean basin, with the purpose of determining the vegetation communities, regions and seasons at which vegetation is driven by drought. Our approach is based on the use of remote sensing data and a multi-scalar drought index. Correlation maps between fields of monthly Normalized Difference Vegetation Index (NDVI) and the Standardized PrecipitationEvapotranspiration Index (SPEI) at different time scales (1-24 months) were compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(128 citation statements)
references
References 74 publications
4
124
0
Order By: Relevance
“…Forests cover approximately 3.7 million hectares (only 1.5% of the land area) in Algeria, half of which are degraded forest or maquis (Pswarayi-Riddihough 2002), concentrated in some wilayas (provinces) of the Northern part of the country, with a negative gradient East-West. Algerian forests are currently in a critical state (DGF 2004) due to human activities (MeddourSahar 2014), which add a negative impact to the extreme climatic factors of the country (heat waves in combination with drought - Duguy et al 2013, Cardil et al 2014, Gouveia et al 2016. Fire, extensive livestock breeding, overgrazing, clearing, illegal forest harvesting, and urbanization contribute to forest degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Forests cover approximately 3.7 million hectares (only 1.5% of the land area) in Algeria, half of which are degraded forest or maquis (Pswarayi-Riddihough 2002), concentrated in some wilayas (provinces) of the Northern part of the country, with a negative gradient East-West. Algerian forests are currently in a critical state (DGF 2004) due to human activities (MeddourSahar 2014), which add a negative impact to the extreme climatic factors of the country (heat waves in combination with drought - Duguy et al 2013, Cardil et al 2014, Gouveia et al 2016. Fire, extensive livestock breeding, overgrazing, clearing, illegal forest harvesting, and urbanization contribute to forest degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the expanse of severe drought events and increasing aridity, along with the rising temperatures and more wildfires, might prompt and exacerbate land degradation processes (Pickup 1998;Reynolds et al 2007), reduce carbon sequestration and enhance more regional warming by the end of century (Huang et al 2015). Given that Mediterranean regions have been highly favored and exploited by humans for habitation, agriculture and recreation (Gouveia et al 2016), and dH changes could result in fundamental shifts in natural ecosystems and human settlements, then there is aggravated risk for food security, and potential for civil conflict and economic decline in the future. For example, Fraser et al (2013) found that wheat and maize production in the northeastern Mediterranean Sea area is extremely vulnerable to increasing dH in the future, because those regional societies have been reducing socioeconomic efforts to adapt to climate change.…”
Section: Projection For the Period 2071-2099mentioning
confidence: 99%
“…The figure shows the natural vegetation in green (15.54%), the crops in yellow (25.55%), the impervious surfaces in red (17.69%), and the bare soil in sienna (28.18%). A cluster analysis is an unsupervised classification method that only classifies the groups on the basis of the similarities among data, so that the cluster analysis procedures are irrelevant to the threshold of the fractions [19,[40][41][42]. Because it has been previously assumed that there exist five categories of typical land uses in the study area (impervious surface, bare soil, natural vegetation, crop, and water) but water regions extracted by MNDWI do not participate in the cluster analysis, four pixel-groups of undefined properties were obtained.…”
Section: Distribution Of Endmember Fractionsmentioning
confidence: 99%